(untitled) (Fiep Bulletin - online, 2015)
The present text aims to tell the metodological ways of the project intitled “TEMPO DE BRINCAR NA PRAÇA”, developed in the XV Festival de Inverno of UFPR in Antonina/PR, on 2005. This action took care of 200 professors of the Municipal Network of Education and aproximately 300 children/day at the age of 06 to 14 years old. Co-ordinated by Teachers of the Departamento de Educação Física, assisted by scholarship holders of the CEPELS/UFPR. This intervention consolidated itslef while extension project, whit practical interventions, in the scope of the leisure-education. Considering the leisure as the culture understood in it wide sense lived (practised or enjoyed) in the conquered time, some contents of the corporal culture was developed, extended and transformed.